1975
DOI: 10.1017/s0022172400024220
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viral infection in childhood. A survey in general practice, Roehampton 1967–1972

Abstract: SUMMARYThe role of viruses and M. pneumoniae in episodes of acute respiratory illness in childhood has been studied in a London general practice. The total isolation rate was 31P7 %, but the rate varied from 32-6 % in upper respiratory infections to 640% in pneumonia. The clinical features associated with infection were influenced not only by the type of agent but also by age and other host factors in the infected children. Rhinoviruses were more commonly isolated than any other agent and were frequently assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
39
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 22 publications
7
39
0
Order By: Relevance
“…Most clinicians consider RSV one of the most important agents of acute respiratory disease in children, and almost 50% of infants are expected to suffer from RSV infection during their first winter (15,16,20,32,35). Inactivated RSV vaccine does not protect against natural infection and leads to an unusual immune response and even lung inflammation during the course of a subsequent natural infection (21).…”
mentioning
confidence: 99%
“…Most clinicians consider RSV one of the most important agents of acute respiratory disease in children, and almost 50% of infants are expected to suffer from RSV infection during their first winter (15,16,20,32,35). Inactivated RSV vaccine does not protect against natural infection and leads to an unusual immune response and even lung inflammation during the course of a subsequent natural infection (21).…”
mentioning
confidence: 99%
“…Specimens were taken immediately to the laboratory and no child was investigated more than 5 days after the onset of symptoms. Horn et al (1975), studying the effect of storage of specimens at 4°C overnight, showed that this did not affect the viral isolation rate. However, a slightly higher isolation rate might have been obtained by more frequent sampling during episodes of wheeze.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between viral infection of the upper respiratory tract and wheeziness has been shown in several studies-hospital inpatients (McIntosh et al, 1973), hospital outpatients (Minor et al, 1974a(Minor et al, , 1976, and general practice (Horn et al, 1975). Some have been confined to the winter months and case selection has been biased by the exclusion of children whose wheezing attacks were thought not to be precipitated by infection (Berkovich et al, 1970;McIntosh et al, 1973;Minor et al, 1974aMinor et al, , 1976.…”
mentioning
confidence: 99%
“…This strongly suggested deficiencies in rhinovirus detection methodology. Secondly, it was shown that early sampling is critical in the successful isolation of viruses [4], and that identification rates tend to be higher in outpatients or subjects from general practice than hospitalised patients and in prospective rather than incidental studies. Finally, only a few studies focused on adults, showing considerably lower overall and rhinovirus-specific identification rates than those obtained in children.…”
Section: Clinical and Epidemiological Evidencementioning
confidence: 99%
“…Nevertheless, probably due to the benign nature of most rhinovirus colds, little attention has been paid to these viruses until recent years, when they have been implicated in acute exacerbations of asthma and chronic obstructive pulmonary disease (COPD). Several early studies sought to objectively establish a link between virus infections and asthma exacerbations [3][4][5]; however, it was only after the advent of PCR-based detection methodologies that it was demonstrated that the vast majority of asthma exacerbations in children [6] and between half to three-quarters in adults [7,8] are associated with respiratory viral infections. In these studies, rhinoviruses were the most frequently identified pathogen.…”
mentioning
confidence: 99%